Intervention of Professional Institutions in Aatmanirbhar Bharth for Rural Development - Mahantesh Halagatti,; Vinayak Banakar, (International Journal of Psychosocial Rehabilitation, 2020)
India, a developing nation is characterized by urban and rural areas. Rural India contributes immensely for the economy with major contribution from agricultural produce and dairy industry. The whole of Urban India is dependent on rural produce for food requirement. Despite the contributions of rural India for the economy, still there is lack of development in rural areas. Basic requirements developed properly can help in uplifting of quality of life in Rural India. With the developmental initiative more productivity can be achieved boosting economic conditions for rural India. This research focuses on identifying the constraints in the development of rural economy. It also attempts to identify roles of professional institutions in rural development. Theory of constraints methodology can be applied in the rural development to make them self-sufficient, self dependent in present scenario.